System Control of Prototype Forklift Using Android and ESP32 Based on MQTT Communication - Faris, Faisal; Sulistiyowati, Indah; Hayatal Falah, Agus; Ahfas, Akhmad (Digital Zone: Jurnal Teknologi Informasi dan Komunikasi, 2024)
This research develops and tests a prototype forklift robot controlled via an Internet of Things (IoT)-based system using an ESP32 microcontroller and the MQTT protocol. Designed to overcome the limitations of traditional manual forklifts, the robot enhances warehouse operations by increasing efficiency and minimizing human error. The study presents the design, testing, and evaluation of the forklift robot's movement control, mechanical wheel performance, load capacity, and wireless connectivity across various Android devices and network providers. Testing was conducted over distances ranging from 1 km to 90 km with different Android devices (e.g., Samsung, Xiaomi, OPPO, Vivo) and providers (Indosat, Axis, Telkomsel, Smartfren). The robot successfully performed a variety of movements, including forward, backward, left, right, rotation, and lifting operations. It demonstrated stable load lifting capabilities up to 300 grams, with instability observed for heavier loads, and could operate smoothly across a range of network conditions. Connectivity tests showed consistent performance and stable communication, reinforcing the robot's practical use for remote control and real-time monitoring. This research emphasizes the potential of IoT-enabled forklift robots to optimize material handling processes in warehouses, contributing to safer and more efficient industrial environments